Design of a Janus‐Faced Electrode for Highly Stretchable Zinc–Silver Rechargeable Batteries. (19th August 2020) - Song, Woo‐Jin; Hwang, Chihyun; Lee, Sangyeop; Kong, Minsik; Kim, Jonghak; Park, Hyung Keun; Son, Hye Bin; Park, Gyeongbae; Cho, Sunghwan; Song, Jun Hyuk; Kim, Hyoung Seop; Jeong, Unyong; et al.
Abstract: One of the biggest challenges facing the development of comfortable wearable electronics is the fabrication of stretchable power sources, which are inherently safe and can maintain their electrochemical performance under mechanical elongation. Zinc–silver batteries based on water‐based chemistry have been investigated as viable power supply candidates, owing to their high energy/power density and safety. However, this type of batteries requires a new electrode that can guarantee both high elasticity and stable cycling characteristics of the battery. Here, stretchable zinc–silver rechargeable batteries based on a Janus‐faced electrode, which is a single electrode that comprises a cathode and an anode, are proposed. The Janus‐faced electrode exhibits good mechanical robustness (200 cycles at 200% strain) and retains a high electrical conductivity in the elongated state (2.1 Ω at 100% strain). A proof‐of‐concept stretchable zinc–silver battery based on the Janus‐faced electrode is fabricated to demonstrate the outstanding long‐term cyclability (capacity retentions of ≈90% after 200 cycles), owing to the prevention of short circuit from the zinc dendrite by the unique electrode configuration. Further, the proposed stretchable zinc–silver batteries can deliver a stable electrochemical performance even under a 200% strain while maintaining their functional properties. Abstract : An intrinsically stretchable Zn‐Ag battery with high energy density, long‐term cyclability, and safety is designed by employing a Janus‐faced electrode comprising a cathode and an anode in the same body. The new stretchable battery exhibits a stable electrochemical performance even under a 200% strain.